A linked-bottleneck control method for urban expressway on-ramp. Issue 2 (20th July 2018) - Jing, Hui-xin; Qian, Wei; Li, Bing-feng; Zhao, Yunji
ABSTRACT: In order to alleviate the congestion in the mainline of urban expressway caused by the uncertainty of the traffic ﬂow, a linked-bottleneck control method for urban expressway on-ramp is proposed in this paper. Firstly, the downstream dynamic critical occupancy of the on-ramp under uncertainty is predicted by using ESN (Echo State Network). Then, a function for dividing the master-slave ramps is designed to dynamically determine the ramp numbers required coordination and expand the range of coordination control. Considering the designed function changes over time and some factors such as the traffic accidents, weather and so on also affect it, the BP neural network is used to improve its accuracy. The proposed method calculates the on-ramp regulating rate based on the downstream dynamic critical occupancy and expand the range of coordination control by the designed function, which can adapt the changes of actual traffic ﬂow and overcome the defects of some methods such as Bottleneck, Linked-control, Swarm and so on. The simulations show that, compared with some existing methods, the congestion duration and the high density duration in the mainline of the urban expressway are signiﬁcantly reduced by using the proposed method in this paper.